2021
DOI: 10.1155/2021/6002949
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Knowledge of Medicinal Plants Used in the Northeastern Part of Morocco

Abstract: The knowledge of the plants that are used may provide insight on their properties for further exploration. This study aimed to identify and collect data about medicinal plants used in traditional medicine by the population of the provincial region of Taza, Morocco. An ethnobotanical survey was carried out among 200 informants, competent villagers, herbalists, and traditional healers from the provincial region of Taza city through direct interviews using a structured questionnaire. The survey reported 55 plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 129 publications
4
21
0
Order By: Relevance
“…It was also noted that women actively participated in this survey (83.49%) compared with men (16.51%). This is in line with previous studies carried out in Morocco, where women were more interested in traditional medicine [ 27 , 28 ]. Unfortunately, most participants did not have formal education (75.69%).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It was also noted that women actively participated in this survey (83.49%) compared with men (16.51%). This is in line with previous studies carried out in Morocco, where women were more interested in traditional medicine [ 27 , 28 ]. Unfortunately, most participants did not have formal education (75.69%).…”
Section: Resultssupporting
confidence: 92%
“…Our results were similar to the only work carried out in Morocco by Salhi et al [ 3 ] on plants used against skin burns. Other work carried out in Morocco on medicinal plants against different pathologies showed that the leaves were the most commonly used parts [ 19 , 27 , 28 , 30 , 68 ]. The results demonstrated that the powder was the main and simplest traditional application method used in the treatment of skin burns either alone or in combination with adjuvants such as honey, olive oil, and rose oil.…”
Section: Resultsmentioning
confidence: 99%
“…vulgare, Mentha pulegium and Allium sativum. Fruits of F. vulgare are used to cure stomach pain and gastrointestinal problems, leaves of M. pulegium are applied to treat the cold and A. sativum is quoted for its cardiovascular proprieties (e.g., to cure hypertension) [78,79]. Among those uses, from phytochemical viewpoint, were studied the fruits of F. vulgare, which have analgesic [80] and carminative [81] properties, therefore its utilization in folk medicine appears also well supported.…”
Section: Medicinal Usesmentioning
confidence: 99%
“…In North Africa, various parts of this tree, such as leaves, stems, roots, fruit, and seeds, have been used in the traditional folk medicine against multiple health conditions. Different parts of the plant have been reportedly prepared in the form of decoction, infusion, fumigation, and paste and applied topically or orally to treat diabetes mellitus, hypertension, diarrhea, rheumatism, intestinal, respiratory, and skin diseases ( Kachmar et al, 2021 ; Idm’hand et al, 2020 ; Amel, 2013 ; Buhagiar et al, 2000 ). Recent studies have lent credence to several ethnomedicinal applications of T. articulata including, antioxidant ( Djouahri et al, 2016 ), antimicrobial ( Bahri et al, 2015 ), anti-inflammatory ( Rached et al, 2018 ), neuroprotective ( El Jemli et al, 2016 ; Sadiki et al, 2018b ), vasorelaxant ( Zidane et al, 2014 ), and anticancer properties ( Calderón-Montaño et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%